Impact of Differential Irrigation on Performance of Onion Cultivated With and Without Plastic Mulching: Performance of onion under differential irrigation - Singh, Mahesh Chand; D. Rajak; Pravin Dahiphale (Journal of Soil Salinity and Water Quality, 2023)
A three-year (2015 to 2018) study was undertaken to monitor the response of differential drip irrigation with and without mulching on growth, yield and water use-efficiency (WUE) of onion cultivated in sandy loam at Zonal Research Station, Darisai, Jharkhand, India. The experiment was laid thrice in a randomized block design with eight treatments viz. T1: drip irrigation at 100% of crop evapotranspiration (ETc), T2: T1 + silver black polyethylene (PE) mulch, T3: drip irrigation at 80% of ETc, T4: T3 + PE mulch, T5: drip irrigation at 60% ETc, T6: T5+ PE mulch, T7: surface irrigation, T8: T7+ PE mulch. Under drip irrigation (with and without PE mulch), plant height, leaves/plant, bulb diameter and yield were recorded on higher sides as compared to surface irrigation alone or with mulch. The yield under drip irrigation (190.94 q/ha) at 80% of ETc was recorded significantly higher when compared with surface irrigation (120.39 q/ha). The use of PE mulch with drip irrigation further enhanced the yield to 232.39 q/ha. The highest and lowest WUE were obtained as 74.76 and 20.48 kg/ha/mm under drip irrigation at 80% ETc with PE mulch and surface irrigation, respectively. Drip irrigation at 80% of ETc resulted in higher net income (113518.70INR/ha) and benefit-cost ratio (B:C=1.52) in onion. Whereas, drip irrigation at 80% of ETc with PE mulch recorded maximum net income (145719.90 INR/ha) and B:C value (1.77). Drip irrigation resulted in water saving and yield increment of about 47 and 48% as compared to surface irrigation.